2003
DOI: 10.1111/1469-8986.00005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temporal changes in cardiac parasympathetic activity and motion sickness severity

Abstract: Chemotherapy-induced nausea has been associated with a time-related decrease in cardiac parasympathetic activity. We tested the hypothesis that a time-related decrease in cardiac parasympathetic activity would also be associated with nausea and other motion sickness symptoms during illusory self-motion (vection). Fifty-nine participants (aged 18-34 years: 25 male) were exposed to a rotating optokinetic drum to induce vection. Symptoms of motion sickness and an estimate of cardiac parasympathetic activity (resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Chemotherapy-induced nausea has been associated with a decrease in cardiac parasympathetic activity. This result leads to the possibility that a decrease in cardiac parasympathetic activity may induce MS symptoms [18]. In our study, the respiratory frequency was uniformly increased by the visual stimuli but did not, however, depend on the stimulus frequency.…”
Section: Discussionmentioning
confidence: 47%
“…Chemotherapy-induced nausea has been associated with a decrease in cardiac parasympathetic activity. This result leads to the possibility that a decrease in cardiac parasympathetic activity may induce MS symptoms [18]. In our study, the respiratory frequency was uniformly increased by the visual stimuli but did not, however, depend on the stimulus frequency.…”
Section: Discussionmentioning
confidence: 47%
“…Research has shown that higher activity of the parasympathetic nervous system before exposure to motion sickness inducing stimuli results in minimal increases in motion sickness (Uijtdehaage et al 1992). Also, studies show reduction in parasympathetic nervous system activity before exposure to motion sickness inducing stimuli consistently leads to the development of motion sickness symptoms during exposure (Hu et al 1991;Gianaros et al 2003). Gianaros et al (2003) demonstrated that a strong negative relationship exists between motion sickness levels and respiratory sinus arrhythmia levels; it is important to note that respiratory sinus arrhythmia is a reliable measure of parasympathetic tone.…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies show reduction in parasympathetic nervous system activity before exposure to motion sickness inducing stimuli consistently leads to the development of motion sickness symptoms during exposure (Hu et al 1991;Gianaros et al 2003). Gianaros et al (2003) demonstrated that a strong negative relationship exists between motion sickness levels and respiratory sinus arrhythmia levels; it is important to note that respiratory sinus arrhythmia is a reliable measure of parasympathetic tone. These data suggest that diminished parasympathetic nervous system activity can precipitate motion sickness symptoms; they also suggest that strategies designed to enhance parasympathetic nervous system activity may be useful in reducing motion sickness symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly surprising was the decrease in respiration rate over time and with increasing motion sickness, which contradicts previous research where slow breathing has been shown to [33,34]. However, Gianaros et al [35] also found decreased respiration rate during optokinetic stimulation, but the decrease was not related to motion sickness severity.…”
Section: Psychophysiologymentioning
confidence: 65%